ANALISIS DISPARITAS PIDANA DALAM KASUS PEMERKOSAAN - Bertin, Bertin (Katalogis, 2016)
The research question were whether or not the criminal disparity in rape cases, already complied with a basic legal value. Accordingly, the objective of the research was to identity the compliance between criminal disparity in rape cases and the basic legal value, and the causes of criminal disparity in rape cases. The research was juridical normative adopting descriptive qualitative method and deductive conclusion. The criminal disparity in rape cases has failed to optimally deliver a basic legal value. Different punishments in the sentences in general has contained a fair justice since the punishment tended to be proportional, in the sense that it complied with the qualification of the alleged crime. However, it lacked of legal certainty and benefits, as the punishment failed to compensate the sorrow of the victim and the embarrassment of her family.Â